Development of Physics Learning E-Module for Class X High School Students - Nur Indriati Harahap; Ramalis Hakim; Rayendra; Ridwan (Postgraduate, University of Mataram, 2024)
This research aims to determine the validity of the physics e-module for grade X Senior High School students. The type of research used is research and development (R&D) by adopting the ADDIE development model. The stages of the ADDIE development model consist of Analysis, Design, Development, Implementation, and Evaluation. Data analysis was conducted to assess the validity of the physics e-module in three aspects: media, content, and language. Validity was evaluated by six experts: two media experts, two content experts, and two language experts. The results of the validity test of the physics e-module obtained from media experts was 79% with the category